Analysis of Interpersonal Communication in the Film '172 Days' in the Role of Nadira Shafa - Nur Hasyim Maulidah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the forms of interpersonal communication depicted in the film 172 Days, with a particular focus on the role of the main female character, Nadzira Shafa. The film is based on a true story that portrays a brief yet deeply meaningful marital relationship between Nadzira and her husband, Muhammad Ameer Azzikra. Using a qualitative approach and content analysis method, this research explores various forms of verbal and nonverbal interactions presented throughout the film's narrative, as well as the emotional and spiritual dynamics underlying the characters’ communication. The findings reveal that interpersonal communication in the film functions not only as a medium for conveying messages but also as a crucial element in fostering emotional closeness, uncovering spiritual meanings, and strengthening character development. Messages conveyed through facial expressions, vocal intonation, body language, and emotionally charged dialogue enrich the audience's understanding of human values in interpersonal relationships. This study is expected to contribute to the development of interpersonal communication studies, particularly in the context of media representation based on real-life stories.